DYNAMICS OF SOCIAL CHANGE IN A MULTICULTURAL SOCIETY - Loso Judijanto; Sulaiman; Eka Mustika Sari; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
In a multicultural society, the complexity of social interactions increases due to the diversity of cultures, languages, religions and norms. This study aims to understand the dianamics of social change in a multicultural society. The research method used in this study is literature that is in accordance with the research context. The results show that multicultural societies that implement inclusive policies from social, economic, technological, and educational aspects reap more harmonious and integrative results. The development of education that recognizes diversity can be crucial in shaping future generations who are ready to thrive in an increasingly plural society. Meanwhile, immigrant integration and economic diversity management are important topics in maintaining social stability.